Apostrophes in Shaping the Image of Christians and Muslims in the Polish Translation of the Book of Contemplation by Usama Ibn Munqidh, Translated by J. Bielawski - Grancow, Patryk; Chyliński, Piotr; Kanas, Rafał; Ludwiczak, Kamil; Maras, Krystian; Agnieszka Gralak (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
This article focuses on the analysis of certain repetitive phrases that have been classified as apostrophes and, depending on their wording, classified as belonging to distinct categories. In the analysis of these apostrophes, several research questions were answered. These were to enable an analysis of whom these phrases referred to, the circumstances of their use, the intensity with which they occurred, how they influenced the perception of Christians, etc. By analyzing these phrases, we can see that Usama ibn Munkidhʼs view of Christians and Muslims is more nuanced.